EFFECT OF GOOD CORPORATE GOVERNANCE AND SUSTAINABILITY REPORT DISCLOSURE STRUCTURE ON COMPANY VALUE AND ECONOMIC ADDED VALUE AS INTERVENING VARIABLE - Aprilia, Erika Astriani (EAJ (Economic and Accounting Journal), 2018)
The purpose of this study to test the effect of Good Corporate Governance Structure, Sustainability Reporting Disclosure,  and Firm Value on the Economic Value Added as an intervening variable. This study uses secondary data from the period 2010-2015 to firms listed at Indonesia Exchange. The sampling technique used purposive sampling. Tools to process the data using SPSS 23.The results showed  Board of Commissioners Size, Independent  Commissioner, Institutional Ownership  have a significant impact on Firm Value while Board of Directors Size, Audit Committee, Managerial Ownership does not have effect on Firm Value. Board of Directors Size and Board of Commissioners Size have an effect on Economic Value Added and Firm Value, but Economic Value Added  not an intervening variable between Board of Directors Size and Board of Commissioners Size. , Independent  Commissioner has not effect on Economic Value Added, but Economic value added is an intervening variable between Independent  Commissioner and Firm Value. Audit Committee does not effect on Economic Value Added and Firm Value, but Economic value added is an intervening variable between Audit Committee and Firm Value. Managerial ownership does not have effect on Economic Value Added and Firm Value, but Economic value added is an intervening variable between Managerial ownership and Firm Value. Institusional Ownership does not have effect on Economic Value Added and Economic Value Added is not intervening variable between Institusional Ownership and Firm Value. Sustainability Report Disclosure has an effect on Economic Value Added and Firm Value.